HADITH UNDERSTANDING METHODS: Study of Hadith Thoughts K.H. Aceng Zakaria in Kitab al-Hidāyah fī Masāil Fiqhiyyah Muta'āriḍah - AZZAHRA, ARINI NABILA (DIRAYAH : Jurnal Ilmu Hadis, 2022)
K.H. Aceng Zakaria became one of the prominent Indonesian ulama as well as Persis who continued to revive the writing tradition, including those related to the study of hadith. In this study, it will be discussed related to the method of understanding the hadith of K.H. Aceng Zakaria through his work, al-Hidāyah fī Masāil Fiqhiyyah Muta'āriḍah. The results of this study indicate that in the method of understanding hadith, K.H. Aceng Zakaria is very concerned about linguistic aspects and the use of uṣul rules in every understanding. Several things can be seen when K.H. Aceng Zakaria explains a hadith. First, understand the hadith according to the instructions of the Qur'anic verse. Second, understand the hadith based on other hadiths. Third, understand the hadith based on its terminology. The terminology can be seen from several expressions, namely expressions that are clear and do not contain other meanings, common lafaz expressions, expressions that contain several meanings (musytarak), and expressions that are concluded in general, deductive and analogical. Fourth, in the resolution of the conflicting hadith in this case K.H. Aceng Zakaria uses one of several methods, namely Jam’u, tarjih, Nasikh, and tawaqquf. Fifth, understanding the hadith based on historical facts, namely understanding the hadith by looking at the cause of the hadith (asbab al-wurūd).